2017
DOI: 10.1038/mp.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnenolone blocks cannabinoid-induced acute psychotic-like states in mice

Abstract: Cannabis-induced acute psychotic-like states (CIAPS) represent a growing health issue, but their underlying neurobiological mechanisms are poorly understood. The use of antipsychotics and benzodiazepines against CIAPS is limited by side-effects and/or by their ability to tackle only certain aspects of psychosis. Thus, safer wide-spectrum treatments are currently needed. Although the blockade of cannabinoid type-1 receptor (CB1) had been suggested as a therapeutical means against CIAPS, the use of orthosteric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 66 publications
(109 reference statements)
0
72
0
Order By: Relevance
“…Our previous data revealed that extended preconditioning training (six odor-taste pairings instead of three) suppresses mediated learning, installing the so-called ''reality testing,'' through which the animals are able to successfully discriminate between stimuli that they initially reacted to in the same way (Busquets-Garcia et al, 2017b;McLaren and Mackintosh, 2002). Notably, extended training also normalizes the hippocampal expression of CB 1 R. Thus, it will be extremely interesting to investigate the causes and the consequences of these molecular adaptations in the training-dependent behavioral switch from mediated learning to ''reality testing'' responses (McDannald and Schoenbaum, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous data revealed that extended preconditioning training (six odor-taste pairings instead of three) suppresses mediated learning, installing the so-called ''reality testing,'' through which the animals are able to successfully discriminate between stimuli that they initially reacted to in the same way (Busquets-Garcia et al, 2017b;McLaren and Mackintosh, 2002). Notably, extended training also normalizes the hippocampal expression of CB 1 R. Thus, it will be extremely interesting to investigate the causes and the consequences of these molecular adaptations in the training-dependent behavioral switch from mediated learning to ''reality testing'' responses (McDannald and Schoenbaum, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…***p < 0.001 (vehicle-versus Rimonabant-treated mice). For statistical details and n, see Tables S1 and S2. taste aversion (Busquets-Garcia et al, 2017b), suggesting that CB 1 R activation is specifically required for the formation of incidental associations, but not for the expression of mediated aversion.…”
Section: Activation Of Cb 1 R During Preconditioning Is Necessary Formentioning
confidence: 99%
See 2 more Smart Citations
“…PSNCBAM-1, for example, elicits acute hypophagic effects (Horswill et al, 2007) and antagonizes neuronal excitability (Wang et al, 2010), properties which may lead to treatments of obesity and some central nervous system (CNS) disorders. Pregnenolone has demonstrated promise in blocking the psychotic-like symptoms such as THC-impaired cognitive function (Busquets-Garcia et al, 2017). Lipoxin A4 has been shown to protect neuronal cells from β-amyloid-induced neurotoxicity (Pamplona et al, 2012), thus demonstrating possible therapeutic potential for the treatment of Alzheimer’s disease.…”
Section: Therapeutic Potential Of Allosteric Modulators Of the Cb1mentioning
confidence: 99%